Planejamento textural a partir de aspectos elementares do caos determinístico aplicados à composição musical - Pontes, Felipe Grisi Correia (2014)
The objective of the present dissertation is the process of a compositional formalization out of the principles of the chaos theory and deterministic chaos in order to structure the textural plan of the pieces Logistic Textures II and TexturalCalc, for string orchestra and chamber orchestra, respectively. The dissertation is divided in three chapters, in which there are relevant musical and mathematical definitions, presentation of the used equations and calculi, both plans and, finally, the description of the compositional procedures of the pieces created during the research. Textural process of conexion and contrast, as well as the concepts of absolut density, relative density and complexity we used. The parameters related to these concepts were mapped according to the chaotic development of some non linear systems, with the aid of an application designed specifically for the task. The systems used were the logistic equation and the preyhunter model. This work aims for a better view of the characteristics of a formalizaed compositional process and the usage of the available resources in the contemporary music.